Ammonia fluorescence sensor and its preparation method and application
By using the chelation of metal ions and liquid crystals and the anchoring effect of surfactants in an ammonia fluorescence sensor, the liquid crystals are arranged vertically, and the complex formed by ammonia and metal ions is used to interfere with the liquid crystal arrangement, the existing technology is solved The complexity and cost of ammonia detection achieve fast, simple and high sensitivity ammonia detection.
Patent Information
- Application Number
- CN202210231889.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-01
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-03-01
AI Technical Summary
The existing ammonia detection methods have problems such as complex preparation process, expensive equipment, and time-consuming processing of nanomaterials, and are not suitable for rapid online detection of ammonia.
Design an ammonia fluorescence sensor, including a substrate, a liquid crystal orientation layer, a grid and a nematic liquid crystal of aggregation-induced luminescent material, to arrange the liquid crystals vertically through the chelation of metal ions and liquid crystals and the anchoring effect of surfactants. , the complex formed by ammonia and metal ions is used to interfere with the arrangement of liquid crystals, resulting in a change in fluorescence intensity to detect ammonia concentration.
It realizes fast, simple and highly sensitive ammonia detection, with a simple structure and low cost, suitable for the detection of ammonia and ammonia water, improving detection sensitivity and selectivity.
Smart Images

Figure CN114813668B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sensor technology, and in particular to an ammonia fluorescence sensor and a preparation method and application thereof. Background Art
[0002] Ammonia is a highly toxic environmental pollutant that is harmful to the human body. It seriously affects the air quality in the formation of secondary inorganic aerosols, and excessive exposure to ammonia can radiate the respiratory tract and cause inflammation, thereby weakening the immune system or causing lung diseases. Therefore, it is very important to effectively detect the presence of trace ammonia.
[0003] In recent years, people have developed a variety of methods for detecting ammonia, such as ammonia detection schemes based on organic semiconductors, metal-organic frameworks, carbon nanotubes, polyaniline nanofibers and graphene oxide. The detection limit of these traditional ammonia detection methods is about 100 ppm, but these detection methods have problems such as complex preparation process, expensive equipment, and time-consuming nanomaterial processing process, which is not conducive to the rapid online detection and practical application of ammonia. Summary of the invention
[0004] The problem solved by the present invention is how to provide a fast, simple and highly sensitive ammonia detection sensor to facilitate the real-time quantitative detection of ammonia.
[0005] To solve at least one aspect of the above problems, the present invention provides an ammonia fluorescence sensor, comprising a substrate, a liquid crystal orientation layer, a grid, a nematic liquid crystal combined with an aggregation-induced emission material, and a surfactant, wherein the liquid crystal orientation layer comprises metal ions, the grid is located on the substrate, the substrate is modified with a liquid crystal orientation layer, the lower part of the nematic liquid crystal combined with the aggregation-induced emission material is combined with the metal ions in the liquid crystal orientation layer, and the upper part of the nematic liquid crystal combined with the aggregation-induced emission material is combined with the surfactant, so that the nematic liquid crystal combined with the aggregation-induced emission material is arranged in an orderly manner perpendicular to the substrate, and the liquid crystal orientation layer and the nematic liquid crystal combined with the aggregation-induced emission material are both located in the grid.
[0006] Preferably, the nematic liquid crystal in the nematic liquid crystal combined with the AIE material comprises 4-pentyl-4'-cyanobiphenyl, and the mass ratio of the nematic liquid crystal in the nematic liquid crystal combined with the AIE material to the AIE material is 999:1.
[0007] Preferably, the liquid crystal alignment layer comprises a metal complex consisting of chitosan and metal ions.
[0008] Preferably, the metal ions include copper ions, and the concentration of the metal ions is 65-175 mM.
[0009] Preferably, the liquid crystal alignment layer is connected to the substrate via a connecting layer, and the connecting layer comprises glutaraldehyde and a silane coupling agent.
[0010] Preferably, the surfactant comprises sodium dodecyl sulfate, and the concentration of the surfactant is 2 mM.
[0011] Preferably, the substrate includes a glass substrate or a quartz substrate.
[0012] The advantages of the present invention compared to the prior art are:
[0013] The present invention arranges a liquid crystal orientation layer with metal ions on a substrate, so that the nematic liquid crystal combined with the aggregation-induced luminescence material can be combined with the metal ions, so that the nematic liquid crystal combined with the aggregation-induced luminescence material can be arranged in an orderly manner perpendicular to the substrate, and the surfactant can also interact with the nematic liquid crystal combined with the aggregation-induced luminescence material, so that the nematic liquid crystal combined with the aggregation-induced luminescence material can be arranged in an orderly manner perpendicular to the substrate by anchoring the nematic liquid crystal up and down at the same time; when ammonia gas is detected, ammonia gas can produce a strong complexation with the metal ions to form a stable metal-ammine complex, thereby replacing the nematic liquid crystal combined with the aggregation-induced luminescence material. The coordination effect between the nematic liquid crystal of the aggregation-induced luminescence material and the metal ions causes the arrangement of the nematic liquid crystal combined with the aggregation-induced luminescence material to be disturbed, and the higher the concentration of the ammonia molecules, the more the coordination numbers replaced, and the nematic liquid crystal combined with the aggregation-induced luminescence material tends to be arranged parallel to the substrate, causing the emission dipole moment of the aggregation-induced luminescence material to tilt, thereby causing its fluorescence intensity to decrease, and the concentration of ammonia can be judged according to the change in fluorescence intensity; the ammonia fluorescence sensor provided by the present invention has a simple structure, low cost, high selectivity and detection sensitivity for ammonia, and can detect ammonia quickly, easily and with high sensitivity.
[0014] Another object of the present invention is to provide a method for preparing an ammonia fluorescence sensor, which is used to prepare the above-mentioned ammonia fluorescence sensor, comprising the following steps:
[0015] Step S1, modifying a liquid crystal alignment layer with metal ions on a substrate to obtain a pretreated substrate;
[0016] Step S2, placing a grid on the pretreated substrate, and then adding a nematic liquid crystal solution combined with an aggregation-induced emission material into the grid, so that the lower part of the nematic liquid crystal combined with the aggregation-induced emission material is arranged in an orderly manner perpendicular to the substrate;
[0017] Step S3, placing the structure obtained in step S2 into a surfactant aqueous solution, so that the upper part of the nematic liquid crystal combined with the aggregation-induced emission material is arranged in an orderly manner perpendicular to the substrate, thereby obtaining an ammonia fluorescence sensor.
[0018] Preferably, the step S1 comprises:
[0019] Step S11, after cleaning the substrate, treating it with piranha solution to obtain a hydroxylated substrate;
[0020] Step S12, immersing the hydroxylated substrate in a silane coupling agent solution to allow the silane coupling agent to combine with the hydroxylated substrate, and then dripping a glutaraldehyde solution onto the hydroxylated substrate to allow the silane coupling agent to connect with the glutaraldehyde;
[0021] Step S13, coating the chitosan solution on the structure obtained in step S12, and then coating the metal ion solution, and obtaining the pretreated substrate after drying.
[0022] The present invention vertically fixes the nematic liquid crystal combined with aggregation-induced emission material on the substrate through the combined effects of metal ion chelation in the liquid crystal orientation layer and surfactant anchoring, which can ensure that the nematic liquid crystal combined with aggregation-induced emission material can also be arranged vertically and orderly relative to the substrate when the thickness is large, thereby making the change of fluorescence intensity more obvious, and can further improve the sensitivity of ammonia detection.
[0023] Another object of the present invention is to provide an application of an ammonia fluorescence sensor, and to apply the above-mentioned ammonia fluorescence sensor to the detection of ammonia gas and ammonia water.
[0024] The ammonia fluorescence sensor provided by the present invention can be used not only for the detection of ammonia gas, but also for the detection of ammonia water, and has high application value in the field of water quality detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of an ammonia fluorescence sensor according to an embodiment of the present invention and a schematic diagram of the sensor in an initial state and an orientation change caused by ammonia;
[0026] Figure 2 The process of the preparation method of the ammonia fluorescence sensor in the embodiment of the present invention is as follows Figure 1 ;
[0027] Figure 3 The process of the preparation method of the ammonia fluorescence sensor in the embodiment of the present invention is as follows Figure 2 ;
[0028] Figure 4 The chemical structure formula of the molecule used to prepare the ammonia fluorescence sensor and the schematic diagram of the pretreatment substrate preparation process in the embodiment of the present invention;
[0029] Figure 5The fluorescence images of the ammonia fluorescence sensor under different SDS concentrations in the initial state and the analysis diagram of the relationship between the SDS concentration and the average fluorescence intensity change in the embodiment of the present invention;
[0030] Figure 6 The fluorescence images of the ammonia fluorescence sensor under different ammonia concentration conditions and the analysis diagram of the relationship between the ammonia concentration and the average fluorescence intensity change in the embodiment of the present invention;
[0031] Figure 7 The fluorescence images of the ammonia fluorescence sensor under different ammonia concentrations and the analysis diagram of the relationship between the ammonia concentration and the average fluorescence intensity change of the embodiment of the present invention are shown;
[0032] Figure 8 This is an analysis diagram of the average fluorescence intensity of the ammonia fluorescence sensor in different gas environments in an embodiment of the present invention. DETAILED DESCRIPTION
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.
[0034] It should be noted that, in the absence of conflict, the features in the embodiments of the present invention can be combined with each other. The meanings of the terms "comprising", "including", "containing", and "having" are non-restrictive, that is, other steps and other ingredients that do not affect the results can be added. The above terms cover the terms "consisting of" and "essentially consisting of". Unless otherwise specified, materials, equipment, and reagents are commercially available.
[0035] An embodiment of the present invention provides an ammonia fluorescence sensor, comprising a substrate, a nematic liquid crystal combined with an aggregation-induced light-emitting material, a surfactant, a grid and a liquid crystal orientation layer, wherein the grid is located on the substrate, the substrate is modified with a liquid crystal orientation layer, the liquid crystal orientation layer comprises metal ions, the lower part of the nematic liquid crystal combined with the aggregation-induced light-emitting material is combined with the metal ions in the liquid crystal orientation layer, and the upper part of the nematic liquid crystal combined with the aggregation-induced light-emitting material is combined with the surfactant, so that the nematic liquid crystal combined with the aggregation-induced light-emitting material is arranged in an orderly manner perpendicular to the substrate, and the liquid crystal orientation layer and the nematic liquid crystal combined with the aggregation-induced light-emitting material are both located in the grid.
[0036] The grid includes a metal grid with a thickness of 10-20 μm. By arranging the metal grid with a thickness of 10-20 μm on the substrate, the liquid crystal alignment layer and the nematic liquid crystal combined with the aggregation-induced luminescence material can be confined within the grid, thereby improving the stability of the sensor, and the thickness is set to 10-20 μm to ensure the performance of the sensor. The grid is preferably set to a TEM grid.
[0037] Specifically, the liquid crystal orientation layer is fixed on the substrate, and the nematic liquid crystal molecules in the nematic liquid crystal combined with the aggregation-induced light-emitting material can be arranged in an orderly manner perpendicular to the substrate through chelation with metal ions, and because the aggregation-induced light-emitting material and the nematic liquid crystal are combined with each other, the aggregation-induced light-emitting material in the nematic liquid crystal combined with the aggregation-induced light-emitting material can also be arranged in an orderly manner perpendicular to the substrate. When the nematic liquid crystal combined with the aggregation-induced light-emitting material is arranged perpendicular to the substrate, the fluorescence intensity generated by ultraviolet light irradiation is the highest, and when the nematic liquid crystal combined with the aggregation-induced light-emitting material is tilted, the fluorescence intensity will decrease to varying degrees; at the same time, the surfactant can also interact with the nematic liquid crystal combined with the aggregation-induced light-emitting material, so that the upper part of the nematic liquid crystal combined with the aggregation-induced light-emitting material can also be arranged perpendicular to the substrate, further ensuring the state of the nematic liquid crystal combined with the aggregation-induced light-emitting material in the initial state.
[0038] For example, the substrate is a glass substrate or a quartz substrate, the nematic liquid crystal in the nematic liquid crystal combined with the aggregation-induced emission material is 4-pentyl-4'-cyanobiphenyl (5CB), the aggregation-induced emission material in the nematic liquid crystal combined with the aggregation-induced emission material is TPE-PPE, and the liquid crystal alignment layer includes chitosan (CHIT) and Cu 2+ The metal complex composed of CHIT-Cu 2+ Complex representation, the surfactant is sodium dodecyl sulfate (SDS), the nitrile group (-CN) in 5CB can react with Cu 2+ Since the liquid crystal alignment layer is fixed on the substrate, 5CB can 2+ The complexation of 5CB makes 5CB vertically arranged in the bottom liquid crystal, while in the upper solution, the surfactant SDS can interact with 5CB, making 5CB also vertically arranged. Since 5CB and TPE-PPE are combined with each other, TPE-PPE is also arranged vertically to the substrate. That is, through the dual anchoring effect of the liquid crystal orientation layer and SDS, 5CB and TPE-PPE can be arranged vertically to the substrate as a whole, ensuring the structural stability. In this way, the thickness of the liquid crystal layer can be increased. When the orientation of the liquid crystal layer changes, the fluorescence intensity changes more significantly, thereby improving the detection sensitivity.
[0039] The weight ratio of the nematic phase liquid crystal to the aggregation-induced emission material in the nematic phase liquid crystal combined with the aggregation-induced emission material is 999:1. 2+ The concentration of Cu is 65-175mM (millimoles per liter), and the concentration of surfactant is 2mM (millimoles per liter). 2+ When the concentration of Cu is 65-175 mM (millimoles per liter), the nematic liquid crystal combined with the aggregation-induced emission material can form a more stable vertical orientation, and Cu2+ The concentration of is preferably set to 150 mM (millimoles per liter). When the concentration of the surfactant is 2 mM (millimoles per liter), the fluorescence intensity is the strongest and reaches a saturation state.
[0040] The liquid crystal alignment layer is connected to the substrate via a connecting layer, and the connecting layer includes glutaraldehyde (GA) and a silane coupling agent. Exemplarily, the silane coupling agent is (3-aminopropyl) triethoxysilane (APTES). First, ATPES can be connected to the substrate via a Si-O-Si covalent bond to obtain a silanized substrate, and the aldehyde group at one end of GA can form a stable connection with the amine group at the end of APTES, and the aldehyde group at the other end of GA can be connected to CHIT, so CHIT-Cu can be connected via GA and ATPES. 2+ The complex is attached to the substrate.
[0041] The detection principle of the ammonia fluorescence sensor provided by the embodiment of the present invention is: in CHIT-Cu 2+ On the complex-modified substrate, the nitrile group (-CN) in the nematic liquid crystal with aggregation-induced emission material is combined with Cu 2+ Complexation makes the nematic liquid crystal with aggregation-induced emission material in the lower part align vertically. In addition, at the interface of the nematic liquid crystal with aggregation-induced emission material and the aqueous solution, the interaction between the surfactant SDS and the nematic liquid crystal with aggregation-induced emission material can make the nematic liquid crystal with aggregation-induced emission material in the upper part align vertically, further ensuring the vertical orientation of the nematic liquid crystal with aggregation-induced emission material. Therefore, the nematic liquid crystal with aggregation-induced emission material can form a vertical orientation under the joint action of copper ions and surfactants. At this time, the fluorescence intensity is the strongest when irradiated with ultraviolet light. When ammonia is present, ammonia can react with Cu 2+ It produces a strong complexation to form a more stable copper-ammine complex [Cu(NH3)4], thereby replacing the nematic liquid crystal and Cu combined with the aggregation-induced emission material. 2+ The coordination effect of ammonia causes the vertical arrangement of the nematic liquid crystal combined with the aggregation-induced emission material to be disturbed, and the higher the concentration of ammonia, the more coordination numbers are replaced, and the nematic liquid crystal combined with the aggregation-induced emission material will tend to be arranged in parallel. In the process of changing the arrangement mode, the emission dipole moment of the aggregation-induced emission material will be tilted. When irradiated with ultraviolet light, the fluorescence intensity will gradually decrease with the degree of tilt. Therefore, the concentration of ammonia can be judged according to the change in fluorescence intensity.
[0042] like Figure 1 As shown, Figure 1 a is a schematic diagram of an ammonia fluorescence sensor, which can emit fluorescence by irradiating the sensor with ultraviolet light; Figure 1b is a schematic diagram of the initial orientation of each molecule in the sensor and the orientation change caused by ammonia. 2+ After complexation, 5CB and Cu 2+ The coordination effect causes the arrangement of the nematic liquid crystal combined with the aggregation-induced emission material to change.
[0043] Another embodiment of the present invention provides a method for preparing an ammonia fluorescence sensor, which is used to prepare the above-mentioned ammonia fluorescence sensor, such as Figure 2 As shown, the following steps are included:
[0044] Step S1, modifying a liquid crystal alignment layer with metal ions on a substrate to obtain a pretreated substrate;
[0045] Step S2, placing a grid on a pretreated substrate, and then adding a nematic liquid crystal solution combined with an aggregation-induced emission material into the grid, so that the lower part of the nematic liquid crystal combined with the aggregation-induced emission material is arranged in an orderly manner perpendicular to the substrate;
[0046] Step S3, placing the structure obtained in step S2 into a surfactant aqueous solution, so that the upper part of the nematic phase liquid crystal combined with the aggregation-induced emission material is arranged in an orderly manner perpendicular to the substrate, thereby obtaining an ammonia fluorescence sensor.
[0047] Among them, Figure 3 As shown, step S1 includes:
[0048] Step S11, after cleaning the substrate, treating it with piranha solution to obtain a hydroxylated substrate;
[0049] Step S12, immersing the hydroxylated substrate in a silane coupling agent solution to allow the silane coupling agent to combine with the hydroxylated substrate, and then dripping the GA solution onto the hydroxylated substrate to allow the silane coupling agent to connect with the GA;
[0050] Step S13, coating the chitosan solution on the structure obtained in step S12, and then coating the metal ion solution, and obtaining a pretreated substrate after drying.
[0051] Specifically, in step S11, the substrate is cleaned with ethanol and isopropanol, treated with piranha solution (H2SO4 and H2O2 in a volume ratio of 7:3) at 80°C for 30 minutes, and then cleaned with deionized water and ultrasonically treated to obtain a hydroxylated substrate.
[0052] In step S12, the hydroxylated substrate is immersed in an ethanol solution containing 1% APTES, blown dry with nitrogen, and heated at 40°C for 3 hours to allow APTES to be bonded to the substrate through Si-O-Si covalent bonds. Then, a 1% GA solution is dropped on the substrate and kept for 1 hour. The excess GA is rinsed with deionized water and dried, so that the aldehyde group at one end of GA and the amine group at the end of ATPES can form a stable connection.
[0053] In step S13, a 0.1% CHIT solution is spin-coated at 1500 r / min on the structure obtained in step S12 to connect CHIT to the aldehyde group at the other end of GA, and then a copper ion solution with a concentration of 65-175 mM is coated on the substrate and dried at 110°C to make CHIT-Cu 2+ The complex is fixed on a glass substrate. The CHIT and copper ion solution are applied step by step to avoid the influence of uneven copper ion distribution and unevenness on the arrangement of nematic liquid crystals combined with aggregation-induced luminescence materials on the substrate surface. When the copper ion concentration is 65mM-175mM, the nematic liquid crystals combined with aggregation-induced luminescence materials can form a stable vertical orientation on the substrate to obtain a pretreated substrate.
[0054] In step S2, a grid is placed on a pretreated substrate, 1 μL of 5CB (99.9 wt%) and TPE-PPE (0.1 wt%) solution are mixed to prepare a mixed solution, and then the mixed solution is dropped into the grid to obtain a nematic liquid crystal combined with an aggregation-induced emission material, wherein the nitrile group (-CN) in the aggregation-induced emission material can react with the Cu on the pretreated substrate. 2+ The complexation allows the nematic liquid crystal combined with the aggregation-induced emission material to be orderly arranged perpendicular to the substrate, wherein the grid is a TEM grid with a thickness of 10-20 μm.
[0055] In step S3, the structure obtained in step S2 is placed in a surfactant aqueous solution, and the SDS anchoring and Cu 2+ Under the combined action of complexation, the nematic liquid crystal combined with the aggregation-induced luminescence material is further ensured to be arranged in an orderly manner perpendicular to the substrate, thereby preparing an ammonia fluorescent sensor. Specifically, the surfactant is SDS.
[0056] Through the combined effects of metal ion chelation in the liquid crystal orientation layer and surfactant anchoring, the nematic liquid crystal combined with the aggregation-induced emission material is vertically fixed on the substrate, which can ensure that the nematic liquid crystal combined with the aggregation-induced emission material can be arranged vertically and orderly relative to the substrate even in the case of a large thickness, thereby making the change in fluorescence intensity more obvious and further improving the sensitivity of ammonia detection.
[0057] Yet another embodiment of the present invention provides an application of an ammonia fluorescence sensor, wherein the ammonia fluorescence sensor is applied to the detection of ammonia gas and ammonia water.
[0058] The ammonia fluorescence sensor provided by the present invention can be used not only for the detection of ammonia gas, but also for the detection of ammonia water, and has high application value in the field of water quality detection.
[0059] The following is a method for preparing an ammonia fluorescence sensor in conjunction with a specific embodiment:
[0060] Example 1
[0061] 1.1. After cleaning the glass substrate with ethanol and isopropanol, treat it with piranha solution (H2SO4 and H2O2 volume ratio of 7:3) at 80°C for 30 minutes, then wash it with deionized water and ultrasonically treat it to obtain a hydroxylated substrate;
[0062] 1.2. Soak the hydroxylated substrate in an ethanol solution containing 1% APTES, blow dry with nitrogen, and heat at 40°C for 3 h to allow APTES to bind to the substrate through Si-O-Si covalent bonds. Then, drop 1% GA solution on the substrate and keep it for 1 h. Rinse the excess GA with deionized water and dry it.
[0063] 1.3. Use 0.1% CHIT solution to spin-coat on the structure obtained in step 1.2 at 1500 r / min, then apply 150 mM Cu(ClO4)2 solution on the substrate, and dry at 110°C to obtain a pretreated substrate;
[0064] 1.4. Place a TEM grid on a pretreated substrate, mix 1 μL of 5CB (99.9 wt%) and TPE-PPE (0.1 wt%) solution to prepare a mixed solution, and then drop the mixed solution into the TEM grid, wherein the thickness of the TEM grid is 10 μm;
[0065] 1.5. Place the structure obtained in step 1.4 in a 2 mM SDS aqueous solution to prepare an ammonia fluorescent sensor;
[0066] in, Figure 4 a is the molecular structure formula of TPE-PPE, 5CB, SDS, CHIT, APTES and GA, Figure 4 b shows the process of obtaining a pretreated substrate after the glass substrate was hydroxylated and then modified with ATPES, GA, CHIT and Cu(ClO4)2 in sequence.
[0067] Example 2
[0068] 2.1. After cleaning the glass substrate with ethanol and isopropanol, treat it with piranha solution (H2SO4 and H2O2 volume ratio of 7:3) at 80°C for 30 minutes, then wash it with deionized water and ultrasonically treat it to obtain a hydroxylated substrate;
[0069] 2.2. Soak the hydroxylated substrate in an ethanol solution containing 1% APTES, blow dry with nitrogen, heat at 40°C for 3 h to allow APTES to bind to the substrate through Si-O-Si covalent bonds, then drop 1% GA solution on the substrate and keep for 1 h, rinse the excess GA with deionized water and dry;
[0070] 2.3, using 0.1% CHIT solution to spin-coat at 1500 r / min on the structure obtained in step 2.2, and then coating the substrate with a 70 mM Cu(ClO4)2 solution, and drying at 110°C to obtain a pretreated substrate;
[0071] 2.4. Place a TEM grid on the pretreated substrate, mix 1 μL of 5CB (99.9 wt%) and TPE-PPE (0.1 wt%) solution to prepare a mixed solution, and then drop the mixed solution into the TEM grid, wherein the thickness of the TEM grid is 15 μm;
[0072] 2.5. Place the structure obtained in step 2.4 in a 2 mM SDS aqueous solution to prepare an ammonia fluorescent sensor.
[0073] Example 3
[0074] 3.1. After cleaning the glass substrate with ethanol and isopropanol, treat it with piranha solution (H2SO4 and H2O2 volume ratio of 7:3) at 80°C for 30 minutes, then wash it with deionized water and ultrasonically treat it to obtain a hydroxylated substrate;
[0075] 3.2. Soak the hydroxylated substrate in an ethanol solution containing 1% APTES, blow dry with nitrogen, and heat at 40°C for 3 h to allow APTES to bind to the substrate through Si-O-Si covalent bonds. Then, drop 1% GA solution on the substrate and keep it for 1 h. Rinse the excess GA with deionized water and dry it.
[0076] 3.3. Use 0.1% CHIT solution to spin-coat on the structure obtained in step 3.2 at 1500 r / min, then apply 165 mM Cu(ClO4)2 solution on the substrate, and dry at 110°C to obtain a pretreated substrate;
[0077] 3.4. Place a TEM grid on the pretreated substrate, mix 1 μL of 5CB (99.9 wt%) and TPE-PPE (0.1 wt%) solution to prepare a mixed solution, and then drop the mixed solution into the TEM grid, wherein the thickness of the TEM grid is 20 μm;
[0078] 3.5. Place the structure obtained in step 3.4 in a 2 mM SDS aqueous solution to prepare an ammonia fluorescent sensor.
[0079] Comparative Example 1
[0080] The difference between this comparative example and Example 1 is that deionized water is used instead of the SDS aqueous solution, and the other conditions are the same as those in Example 1.
[0081] Comparative Example 2
[0082] The difference between this comparative example and Example 1 is that the concentration of the SDS aqueous solution is 0.5 mM, and the other conditions are the same as those in Example 1.
[0083] Comparative Example 3
[0084] The difference between this comparative example and Example 1 is that the concentration of the SDS aqueous solution is 1 mM, and the other conditions are the same as those in Example 1.
[0085] Experimental Example 1
[0086] The influence intensity of the ammonia fluorescence sensor prepared in Example 1 and Comparative Examples 1-3 in the initial state was tested respectively. The testing method was as follows: the ammonia fluorescence sensor was irradiated with 365nm ultraviolet light, and a fluorescence image was collected by a CCD camera, wherein the illumination intensity of the ultraviolet light was 10mW / cm 2 The test was conducted at room temperature (25°C) and humidity of 60%. Figure 5 shown.
[0087] Figure 5 a is the fluorescence image of different ammonia fluorescence sensors, Figure 5 b is the relationship between different SDS concentrations and the average fluorescence intensity. Figure 5 It can be seen from ae that with the increase of SDS concentration, the fluorescence intensity of the ammonia fluorescence sensor after ultraviolet light irradiation gradually increases, and when the SDS concentration is 2mM, the average fluorescence intensity is the highest and reaches the saturation intensity.
[0088] Experimental Example 2
[0089] The fluorescence intensity of the ammonia fluorescence sensor prepared in Example 1 under conditions of different ammonia concentrations was detected, and a calibration curve was fitted according to the changes in ammonia concentration and fluorescence intensity.
[0090] The specific detection method is as follows: the ammonia fluorescence sensor prepared in Example 1 is placed in a 500 mL perforated gas chamber, ammonia water is heated to obtain ammonia of different concentrations, and then the ammonia fluorescence sensor is tested under different ammonia concentrations with an intensity of 10 mM / cm 2 Under the irradiation of 365nm ultraviolet light, the sensor emits 450nm fluorescence, and the fluorescence image is collected by the CCD camera. Among them, the ammonia concentration at standard atmospheric pressure (1atm) obtained by heating ammonia water is calculated by the following formula:
[0091]
[0092] ρ is the density of ammonia water, is the volume of ammonia water (25%), is the volume of the gas chamber; all tests were carried out at room temperature (25°C) and humidity of 60%; the detected ammonia concentration range was 0-1600ppm, and the fluorescence intensity was tested under ammonia concentrations of 0, 20, 100, 300, 500, 1000, 1300 and 1600ppm respectively.
[0093] like Figure 6 As shown, Figure 6 ah is the fluorescence image of the ammonia fluorescence sensor under different ammonia concentrations, Figure 6 i is the relationship between ammonia concentration and average fluorescence intensity. The calibration curve is obtained by fitting the corresponding relationship between ammonia concentration and average fluorescence intensity. The fitting result is I = -0.061*C(NH 3 ) +155.623 (R 2 =0.97) , where C(NH3) is the concentration of ammonia. The detection limit is calculated to be 5.4ppm using LOD=3σ / S as the standard, where σ is the standard deviation of multiple measurements of blank samples, and S is the slope of the calibration curve. The detection range is from 0-1600ppm, which is significantly lower than the detection limit of about 100ppm of traditional ammonia detection methods.
[0094] Experimental Example 3
[0095] The fluorescence intensity of the ammonia fluorescence sensor prepared in Example 1 was detected under conditions of different ammonia concentrations, and a calibration curve was fitted according to the changes in ammonia concentration and fluorescence intensity.
[0096] The specific detection method is: the ammonia fluorescence sensor prepared in Example 1 is placed in ammonia water of different concentrations for detection; the ammonia concentration range of the detection is 0-560ppm, and the intensity is 10mM / cm 2Under the irradiation of 365nm ultraviolet light, the sensor emits 450nm fluorescence, and the fluorescence image is collected by a CCD camera. The fluorescence intensity is tested under the conditions of ammonia concentration of 0, 80, 160, 300, 240, 320, 400, 480 and 560ppm.
[0097] like Figure 7 As shown, Figure 7 ah is the fluorescence image of the ammonia fluorescence sensor under different ammonia concentrations, Figure 7 i is the relationship between ammonia concentration and average fluorescence intensity. The calibration curve is obtained by fitting the corresponding relationship between ammonia concentration and average fluorescence intensity. The fitting result is I = -174.44·ln[C(NH 4 OH)] +151.32 (R 2 =0.97) , where C(NH4OH) is the concentration of ammonia water, the detection range is from 0-560ppm, and the detection limit is 1.8ppm. This shows that the ammonia fluorescence sensor provided in Example 1 is not only suitable for the detection of ammonia gas, but also suitable for the detection of ammonia water concentration, and has a high detection sensitivity.
[0098] Experimental Example 4
[0099] The ammonia fluorescence sensor prepared in Example 1 was subjected to a selectivity test. The sensor was placed in an environment of 1000 ppm SO2, CO2, Cl2, H2S and 700 ppm NH3, respectively. 2 The sensor was irradiated with 365nm ultraviolet light and the fluorescence image was collected by a CCD camera. The test was carried out at room temperature (25℃) and 60% humidity, and the change in the average fluorescence intensity of the sensor was calculated.
[0100] from Figure 8 It can be seen that compared with 700ppm NH3, the sensor has a lower response to other gases with higher concentrations (1000ppm), indicating that the sensor has good selectivity for ammonia.
[0101] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. An ammonia fluorescence sensor, characterized in that: The invention comprises a substrate, a liquid crystal alignment layer, a grid, a nematic liquid crystal combined with an aggregation-induced light-emitting material, and a surfactant, wherein the grid is located on the substrate, the substrate is modified with a liquid crystal alignment layer, the liquid crystal alignment layer comprises metal ions, the lower part of the nematic liquid crystal combined with the aggregation-induced light-emitting material is combined with the metal ions in the liquid crystal alignment layer, and the upper part of the nematic liquid crystal combined with the aggregation-induced light-emitting material is combined with the surfactant, so that the nematic liquid crystal combined with the aggregation-induced light-emitting material is arranged in an orderly manner perpendicular to the substrate, and the liquid crystal alignment layer and the nematic liquid crystal combined with the aggregation-induced light-emitting material are both located in the grid; The nematic liquid crystal in the nematic liquid crystal combined with the aggregation-induced light-emitting material comprises 4-pentyl-4'-cyanobiphenyl, and the mass ratio of the nematic liquid crystal in the nematic liquid crystal combined with the aggregation-induced light-emitting material to the aggregation-induced light-emitting material is 999:1; the liquid crystal orientation layer comprises a metal complex composed of chitosan and metal ions; the liquid crystal orientation layer is connected to the substrate through a connecting layer, and the connecting layer comprises glutaraldehyde and a silane coupling agent.
2. The ammonia fluorescence sensor according to claim 1, characterized in that: The metal ions include copper ions, and the concentration of the metal ions is 65-175 mM.
3. The ammonia fluorescence sensor according to claim 1, characterized in that: The surfactant includes sodium dodecyl sulfate, and the concentration of the surfactant is 2 mM.
4. The ammonia fluorescence sensor according to claim 1, characterized in that: The substrate includes a glass substrate or a quartz substrate.
5. A method for preparing an ammonia fluorescence sensor, used to prepare the ammonia fluorescence sensor according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step S1, modifying a liquid crystal alignment layer with metal ions on a substrate to obtain a pretreated substrate; Step S2, placing a grid on the pretreated substrate, and then adding a nematic liquid crystal solution combined with an aggregation-induced emission material into the grid, so that the lower part of the nematic liquid crystal combined with the aggregation-induced emission material is arranged in an orderly manner perpendicular to the substrate; Step S3, placing the structure obtained in step S2 into a surfactant aqueous solution, so that the upper part of the nematic liquid crystal combined with the aggregation-induced emission material is arranged in an orderly manner perpendicular to the substrate, thereby obtaining an ammonia fluorescence sensor.
6. The method for preparing the ammonia fluorescence sensor according to claim 5, characterized in that: The step S1 comprises: Step S11, after cleaning the substrate, treating it with piranha solution to obtain a hydroxylated substrate; Step S12, immersing the hydroxylated substrate in a silane coupling agent solution to allow the silane coupling agent to combine with the hydroxylated substrate, and then dripping a glutaraldehyde solution onto the hydroxylated substrate to allow the silane coupling agent to connect with the glutaraldehyde; Step S13, coating the chitosan solution on the structure obtained in step S12, and then coating the metal ion solution, and obtaining the pretreated substrate after drying.
7. An application of an ammonia fluorescence sensor, characterized in that: The sensor prepared by the ammonia fluorescence sensor as described in any one of claims 1 to 4 or the preparation method of the ammonia fluorescence sensor as described in any one of claims 5 to 6 is applied to the detection of ammonia gas and ammonia water.
Citation Information
Patent Citations
Ammonia gas sensor, production method thereof, and ammonia gas detection system
CN105938104A
Liquid crystal-based detection probe and preparation method and application thereof
CN111982902A